How multifunctional farmland use shapes heterogeneous farmland renting-out behavior in rural China: institutional path dependence and threshold effects - Wang, Yayun; Cai, Yinying (Frontiers in Sustainable Food Systems, 2025)
Farmland in aging societies increasingly serves dual roles as a productive asset and an intergenerational safety net, creating institutional path dependence that drives heterogeneous household responses to multifunctional farmland use (MFU). This study constructs Revealed Comparative Advantage (RCA) indices to quantify the structural balance of MFU across four functions: Economic Contribution (ECF), Food Supply (FSF), Pension Security (PSF), and Employment Security (ESF). A threshold regression model was employed to identify nonlinear effects of MFU on farmland renting-out, while mediation analysis elucidated underlying mechanisms. Key findings reveal: (1) An inverted U-shaped relationship between MFU intensity and farmland renting-out, with a tipping point at Total Functional Score (TFS) = 0.056. Higher intensity inhibits farmland renting-out for farming households (β = −0.208, p < 0.01) but promotes farmland renting-out for off-farming households (β = 9.015, p < 0.05); (2) Functional imbalances universally drive renting-out, exerting three-fold stronger effects on off-farming households (β = 0.477 vs. 0.158), where synergy between the economic contribution function (ECF) and pension security function (PSF) amplifies these imbalances while farming households resist farmland renting-out through employment security function (ESF)-PSF trade-offs. These effects are amplified by synergies between the ECF and PSF, while farming households counter farmland renting-out pressures through trade-offs between ESF and PSF. These results demonstrate how institutional-socioeconomic interactions (e.g., collective ownership and urban-rural welfare gaps) bifurcate land-use decisions. We advocate context-specific governance, such as "land- for-pension" schemes in Key Ecological Zones and ECF-optimized leasing in development zones to reconcile multifunctionality with sustainable transitions. This provides actionable pathways for agrarian economies navigating aging and urbanization globally, bridging land-use efficiency and intergenerational equity in pursuit of Sustainable Development Goals.